Inovasi Aplikasi Sistem Informasi Laundry Sepatu Dengan Menggunakan Metode Waterfall - Nahriyan Zidan Bahar Rizqi; Sumarno Sumarno; Ade Eviyanti; Nuril Lutvi Azizah (SMATIKA JURNAL : STIKI Informatika Jurnal, 2024)
The method of checking shoe clothing carried out by most clients is still conventional. Clients still got to check with the shoe clothing put to begin with. With this strategy, there are still a few issues that happen, particularly the time and vitality went through in carrying out the checking prepare gets to be incapable and wasteful. This inquire about points to plan and construct a web-based data framework utilizing the Waterfall strategy. The data framework that has been built can fathom and give development for issues that happen with respect to checking shoes that have not been or have been prepared rapidly and make it less demanding for clients to get data almost the shoe clothing process via the net. The data framework is outlined based on the stages contained within the Waterfall strategy. In the mean time, the data framework improvement handle employments the Visual Code Studio application and MySQL database.